Penerapan budidaya hijauan pakan melalui pertumbuhan leguminosa merambat pada praktikum mahasiswa di kebun hijauan makanan ternak: Application of forage cultivation through the development of cover crop leguminosae in a forage garden by students - Diana Sawen; Lambertus E. Nuhuyanan; Bambang Tj. Hariadi; Onesimus Yoku; Caroline D. Ariana; Mikael G. Sallosa; Yohanis P. E. A. Nurak; Norma Y. Nouwenik; Bayu Rifai; Linkolin Soe; Yoppy Kafiar; Emma F. Kendy; Jeinuddin M. R. M. Iha; Agustinus Y. Vuin; Gaby Fonataba; Daud Keiya; Rika L. A. Waliana; M. Abdurahim (IGKOJEI: Jurnal Pengabdian Masyarakat, 2023)
ABSTRACT  Providing forage for livestock in adequate quantities and continuously available is the aim of forage cultivation. This student project was carried out to provide education based on practice and offer forage cultivation information for the farmer. Three species of legume have been planted which consist of Arachis glabrata, Centrosema pubescens, and Clitoria ternatea. Those legume are good quality forage for the livestock. Descriptive methods has been applied  with trial plot of legume and direct observation on the field. The project has been carried out in the animal farm of the Faculty of Animal Husbandry of Papua University in Manokwari. The porject run for three months. The results showed that simultaneously, the three legume species increased plant growth and growth rates in the form of the number of leaves, the number of tillers, and the length of the tendrils, which increased with the time of observation. Forage cultivation actually aims to provide forage of good quality in adequate quantities and continuously available for livestock according to their needs. This learning program actually also aims to provide education to students participating in the course and, in general, to breeders about how to cultivate forage in the form of creeping leguminosae, including Arachis glabrata, Centrosema pubescens, and Clitoria ternatea. The method used is descriptive, with the techniques of making demonstration plots or observation plots, discussion, and direct observation. The activity lasted for 3 months and was located in the HMT plantation area owned by the Faculty of Animal Husbandry, UNIPA Manokwari. The results showed that simultaneously, the three legume species increased plant growth and growth rates in the form of the number of leaves, the number of tillers, and the length of the tendrils, which increased with the time of observation.  Keywords: Cover crop legume; Forages; Growth   ABSTRAK   Budidaya hijauan pakan ternak sebenarnya bertujuan untuk menyediakan hijauan pakan yang berkualitas baik, dengan jumlah yang memadai dan tersedia berkesinambungan bagi ternak sesuai dengan kebutuhannya. Program pembelajaran ini sebenarnya juga bertujuan untuk memberikan edukasi kepada mahasiswa peserta mata kuliah dan juga secara umum kepada peternak tentang bagaimana melakukan budidaya hijauan pakan berupa leguminosa merambat, diantaranya Arachis glabrata, Centrosema pubescens dan Clitoria ternatea. Metode yang digunakan adalah deskriptif dengan teknik pembuatan demplot atau petak pengamatan, diskusi dan observasi langsung. Kegiatan berlangsung selama 3 bulan yang berlokasi di lahan kebun HMT milik Fakultas Peternakan UNIPA Manokwari. Hasil kegiatan menunjukkan bahwa secara simultan ketiga spesies legume memberikan peningkatan pertumbuhan tanaman dan laju pertambahan berupa jumlah daun, jumlah anakan dan panjang sulur yang semakin besar seiring dengan waktu pengamatan. Kata kunci: Hijauan pakan; Legume cover crop; Pertumbuhan